Guerrilla marketing: a qualitative study on Generation Z, exploring perceptions and loyalties around fast food advertising - Rogers, Devonn (The IIE, 2022)
This interpretivist, qualitative study looked to understand how guerrilla marketing shifts Gen Z perceptions and loyalties of fast food brands. This study was rooted in the theoretical foundation of consumer behaviour, therefore understanding how individuals aged 18-25 have their consumer behaviour shifted once they had experienced guerrilla marketing. New marketing strategies are needed to combat traditional marketing’s downfalls, this being information overload, lowered success in engagement and dwindling consumer loyalty (Klepek, 2014). This research has addressed the search for new marketing strategies that is a result of the shift in changing consumer needs (Kotler, 2017), specifically unpacking guerrilla marketing as an effective strategy to shift consumer perceptions and reinforce existing consumer loyalties. This was done to further the understanding of guerrilla marketing by exploring consumer behaviour, perceptions and loyalties through telephonic in-depth, semi-structured interviews of 8 participants who met the sample and population characteristics. After a pilot study and 8 interviews, data saturation occurred. Data was inductively and thematically analysed, open coding was used to code the transcribed audio data. The process was iterative, preliminary coding, and two coding cycles were conducted to ensure sound analysis. The key insight arriving from this was guerrilla marketing is an effective marketing strategy in creating positive a brand image and brand associations, while also placing brands that use this marketing at the top of the consumers mind in the context of fast food brands. Furthermore, it was understood that guerrilla marketing had the ability to reinforce existing brand loyalties but in itself cannot produce brand loyalty, only positive brand perceptions. It was noted that guerrilla marketing made brands seem more creative, engaging and clever. The contribution to this field was to lend to the discussion around a better understanding of guerrilla marketing as a tactic, this is important as traditional marketing is becoming obsolete and messages are being lost in the saturated marketplace (Kumar, 2015). Hopefully bettering marketing campaigns and decisions, thus contributing to the fields of marketing and academia in expanding the accessible knowledge of this topic.
Keywords: Generation Z; Digital marketing; Buying patterns